Trade, Development, and the Political Economy of Public Standards - Johan F.M. Swinnen; Thijs Vandemoortele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
This paper presents a political economy model of public standards in an open economy model. We use the model to derive the political optimum and to analyze different factors that have an influence on this political equilibrium. The paper discusses how the level of development influences the political equilibrium. We also analyze the relation between trade and the political equilibrium and compare this political outcome with the social optimum to identify under which cases `under-standardization?or `over-standardization?results, and which standards can be labeled as (producer)protectionist measures.
Keywords: F13; F59; H49; L15; O1; 330; standards; political economy; trade; development; Produktqualität; Normung; Wohlfahrtsanalyse; Protektionismus; Offene Volkswirtschaft; Theorie